Subject preferences of sixth-grade children - Eduave, Leonardo C. 1940- (1965)
A study on subject preferences of grade 6 children was carried out in four randomly selected representative schools in Manila. The data-gathering instrument was a two-page checklist. Respondents included 1,514 boys and girls. Statistical methods employed in the analysis of data were the rank correlation and chi-square formulas. The conclusions drawn from the study were: children seem to express definite, wide-ranging attitudes of favorable and unfavorable nature for their school subjects; significant differences exist for the attitudes of boys and girls; and preferences were positively related to assigned attributes of subjects.
"September, 1965."
Vita.
Thesis (M.A. Education)--University of the Philippines, Diliman
Keywords: Sixth grade (Education) -- Philippines -- Manila; Education, Elementary -- Philippines -- Manila -- Curricula; School children -- Philippines -- Manila -- Attitudes